Perlindungan Konsumen Digital Global melalui Harmonisasi Regulasi Transaksi B2C Lintas Batas - Dutasena Mahardhika Hadi (PT. Saha Kreasi Indonesia, 2026)
The rapid development of digital technology has significantly increased cross-border electronic commerce transactions, particularly in the Business-to-Consumer (B2C) scheme. While this phenomenon creates global economic opportunities, it also raises various legal issues, especially regarding the inadequate protection of digital consumers. Differences in legal systems, protection standards, and dispute resolution mechanisms across countries place consumers in a vulnerable position. This study aims to analyze the urgency of regulatory harmonization in cross-border B2C transactions as an effort to strengthen global digital consumer protection. The research method used is normative juridical with comparative law and conceptual approaches. The results indicate that the absence of uniform international regulations leads to legal uncertainty and difficulties in enforcing consumer rights. Therefore, regulatory harmonization through international legal instruments and intergovernmental cooperation is necessary to establish effective and adaptive protection standards in line with digital developments. In conclusion, regulatory harmonization is a strategic step to ensure legal certainty and enhance consumer trust in global digital transactions.